Unilateral knee and ankle joint fatigue induce similar impairment to bipedal balance in judo athletes - Ghram, A.; Young, J. D.; Soori, R.; Behm, D. G. (Journal of Human Kinetics, 2019)
The purpose of this study was to compare the effects of unilateral ankle fatigue versus the knee muscles with and without vision on bipedal postural control. Elite judo athletes who competed at the national level with at least 10 years of training experience, were randomised into KNEE (n = 10; 20 ± 2 years) and ANKLE (n = 9; 20 ± 3 years) groups, who performed dynamic isokinetic fatiguing contractions (force decreased to 50% of initial peak torque for three consecutive movements) of the knee flexors and extensors or ankle dorsiflexors and plantar flexors, respectively. Static bipedal postural control (French Posturology Association normative standards) with eyes open and eyes closed was examined before and immediately after the fatiguing task. Postural variables examined were the centre of pressure (CoP) sway in the medio-lateral and antero-posterior directions, total CoP area sway and CoP sway velocity. Although unilateral ankle and knee fatigue adversely affected all bipedal postural measures, with greater disturbances with eyes closed, there were no significant main group or interaction effects between KNEE and ANKLE groups. Unilateral lower limb fatigue adversely affected bipedal balance, with knee extension/flexion fatigue affecting bipedal postural control to a similar extent as unilateral ankle dorsiflexion/plantar flexion fatigue. Hence unilateral fatigue can affect subsequent bilateral performance or also have implications for rehabilitation exercise techniques. Our findings may be limited to judo athletes as other populations were not tested.